2005
DOI: 10.5993/ajhb.29.2.9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peer Social Network Factors and Physical Activity in Adolescent Girls

Abstract: Objective-To study the relationship between peer-related physical activity (PA) social networks and the PA of adolescent girls.Methods-Cross-sectional, convenience sample of adolescent girls. Mixed-model linear regression analyses to identify significant correlates of self-reported PA while accounting for correlation of girls in the same school.Results-Younger girls were more active than older girls. Most activity-related peer social network items were related to PA levels. More PA with friends was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 18 publications
7
111
0
4
Order By: Relevance
“…Sharing has been shown to have a positive relationship with inducing change of behaviour as a result of social pressure, support and accountability among members of a group [127,128]. However, some of the studies that have incorporated this feature into their applications have reported issues that resulted from sharing such as unhealthy competitiveness [129], negative impacts if a desired response from peer was not received [30] and breach of privacy.…”
Section: Emerging Issues and Future Research Directionsmentioning
confidence: 99%
“…Sharing has been shown to have a positive relationship with inducing change of behaviour as a result of social pressure, support and accountability among members of a group [127,128]. However, some of the studies that have incorporated this feature into their applications have reported issues that resulted from sharing such as unhealthy competitiveness [129], negative impacts if a desired response from peer was not received [30] and breach of privacy.…”
Section: Emerging Issues and Future Research Directionsmentioning
confidence: 99%
“…For example, improving the condition of school fields, making them available for use outside of school hours, ensuring safe access, and providing supervision support the formation of social networks and involvement in structured physical activity both during and after school. 30,39,40 Geocaching, an activity during which individuals or groups search for items described on Web sites using navigational tools, such as GPS tracking devices, also leverages social networks and the built environment to increase physical activity. Thus, participation encourages both social networking and outdoor activity.…”
Section: The Role Of the Built Environmentmentioning
confidence: 99%
“…The majority of studies have shown that significant adults and friends in an adolescent's life are important agents of socialization into physical activity both as role models and through encouragement and support [14,[21][22][23][24][25]. They also provide instrumental and tangible support in providing transportation to activities and paying activity fees.…”
Section: Introductionmentioning
confidence: 99%